Caravaggio - Wilson-Smith, Timothy. 1936- (Colour Library., 1998)
Michelangelo Meresi da Caravaggio (1571-1610) was a boldly original artist who led a short and violent life. His sexually provocative nude figures and his dramatic religious paintings have a psychological power and an undiminished capacity to shock and disturb after almost four centuries. Timothy Wilson-Smith provides a lively and readable biography of an artist who has become an iconic figure in the late twentieth century, and presents a memorable selection of his works, from his early genre pictures to the dark and intense religious paintings of his years in exile.